Praktik Rantai Pasok Berkelanjutan: Penerapan Milk Run di Industri Plastik - Soesilo, Rahman; Valentine, Adelia; Sulistyo, Suryo (Institut Transportasi dan Logistik Trisakti, 2024)
This study aims to explore the impact of implementing the Milk Run method in supply chain of plastic industry in PT RPI. By reducing the distance of 48 km per day, equivalent to 1,200 km in a month of deliveries, the research highlights significant changes in logistics’ efficiency, cost savings, and carbon emission reduction. More connected travel patterns allow trucks to combine pick-ups or deliveries of multiple sources in single trip to enhance the overall logistics’ efficiency. Reducing the distance contributes to saving transportation’s cost by lowering fuel consumption and maintaining vehicle expenses. Reducing a 1,200 km distance, assumed that a fuel consumption rate of 7 km per liter and a carbon emission rate of 2.68 kg CO2 per liter, could result in a substantial carbon emission reduction. This study provides a foundation for further research, including route and scheduling optimization, in-depth environmental impact analysis, and Milk Run implementation in other industries. The findings offer a comprehensive overview of Milk Run effectiveness in the plastic industry, emphasize operational advantages, economic impact, and commitment to sustainability.